What’s science got to do with it? Meet the first cohort from the CGIAR Food Systems Accelerator Program - Zulu-Hume, Mercy F.; Ng'ang'a, Salome (CGIAR System Organization, 2023)
Blog introducing the objective of the CGIAR Food Systems Accelerator (CFSA) program and first cohort.